Groundwater management and protection in Denmark: a review of pre-conditions, advances and challenges - Jorgensen, L.F.; Villholth, Karen G.; Refsgaard, J.C. (Informa UK Limited, 2017)
Denmark is making continuous efforts to attain sustainable groundwater management. With groundwater constituting virtually the only resource for all water uses, groundwater management was addressed early on and has progressed over the last century. This article gives an overview of the advances, along with past and present challenges in securing sustainable groundwater utilization. The objective is to document comprehensively the Danish case and to highlight some of the unique conditions and principles that have shaped and facilitated groundwater management in the country.